EFFECT OF DUKU (Lansium domesticum Corr) SEED EXTRACT ON URINATION ALLOXAN INDUCED DIABETIC RATS - sri hidayati hidayati (Majalah Kedokteran Sriwijaya, 2021)
ABSTRACT Duku seed extract has hypoglycemic effect. The result of phytochemical screening showed the presence of flavonoid, triterpen and saponin. To determine the effect, the clinical trial was carried out on alloxan induced diabetic rats. The aims of study is to determine of effect duku seed extract to urination on alloxan induced diabetic rats. Experimental study with pre-and post-test with control group design was carried out at Laboratory Chemistry Analysis MIPA Faculty and Animal House at Faculty of Medicine Sriwijaya University University in January 2014 to March 2014. The study subject were 30 male white rats 2-aged 3 months and weight 200-250 g. Rats were made diabetes by intraperitoneal administration of 160 mg/kg of alloxan. All rats divided into five groups, K1 which is negative control were treated with aquadest, K2 treated with duku seed extract 100mg/kgbw, K3 treated with duku seed extract 200mg/kgbw, K4 treated with duku seed extract 300mg/kgbw, and K5 treated with glimepiride 0,018mg/kgbw at single dose per day for a period of 14 days. The data obtained was analyzed with normality test, paired sample t test, ANOVA, and Post Hoc test by using SPSS version 20.Data of blood glucose, body weight, and urine volume have normally distribution. All subject have blood glucose >200mg/dL Duku seed extract and glimepiride can decreased urine volume in alloxan-induced diabetes rats. Duku seed extract dose 100 mg/kgbw were no significant difference (P <0.05) between glimepiride to decreased volume urine on 11th  and 15thdays.It can be concluded that low dose of duku seed extract can be used to decreased urine volume on alloxan induced diabetio rats.